The Influence Of Teacher’s English Talk In Teaching English Toward The Students’ Speaking Ability At The Second Year Students Of SMA 1 Wonomulyo - Nurliah, Nurliah (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2018)
This research attemps to find out the influence of teacher’s English talk in teaching toward students’ speaking ability. The objective of research is to get information about the teacher’s English talk at SMA Negeri I Wonomulyo and whether or not the English teacher’s talk in teaching influence the students’ speaking ability.The method used in this research is descritive. The sample of this research XI IPA 2, the total sample were 45 students at the second year students SMA Negeri I Wonomulyo and one of the English teacher by using cluster random sampling. The result of analysis shows that the teacher’s English talk in teaching gives the positive influence toward students’ speaking ability, the students speaking ability increase thus the students at SMA Negeri I Wonomulyo have a good speaking, it is proved by result of students’grades for speaking skill in learning which is classified as good classification (the main score is 71,82).